Jejak Digital dan Jiwa Remaja: Pengaruh Media Sosial terhadap Kesehatan Mental - Putri Adella Cahyaningtyas; Binastya Anggara Sekti (Prosiding SISFOTEK, 2024)
In this digital era, social media has become an integral part of everyday life, especially among teenagers. Digital traces left by users on social media cover a wide range of online activities, from uploading photos and videos to interactions with other content. This study highlights how these digital traces can affect the psychological condition of teenagers. Excessive use of social media can cause stress, anxiety, and depression. The pressure to always look perfect, get ‘likes’ and positive comments can cause feelings of insecurity and low self-esteem. In addition, exposure to cyberbullying and negative content also has a negative impact on teenagers’ mental well-being. However, social media also has positive sides, such as increasing social connectedness and providing a platform for self-expression. This article aims to examine various factors that influence adolescent mental health through the use of social media. By understanding the relationship between digital footprints and mental health, it is hoped that effective strategies can be found to minimize the negative impacts and maximize the benefits of using social media. Education about the wise use of social media as well as support from family and the surrounding environment are very important in maintaining the mental health of teenagers in this digital era.